2019
DOI: 10.1063/1.5088655
|View full text |Cite
|
Sign up to set email alerts
|

Generation and metastability of deep level states in β-Ga2O3 exposed to reverse bias at elevated temperatures

Abstract: Impact of proton irradiation on conductivity and deep level defects in-Ga 2 O 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Notably, E * 2 has also been observed in as-grown β-Ga 2 O 3 thin-films deposited by MBE, and was found to significantly impact the performance of MESFETs comprising these thin-films [98,106]. Recently, it has been reported that a number of defects are created in β-Ga 2 O 3 at elevated temperatures when an electrical field is present inside the material [104]. This finding has great implications for β-Ga 2 O 3 -based devices and their longterm operation.…”
Section: Influence Of Defects On the Electrical Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, E * 2 has also been observed in as-grown β-Ga 2 O 3 thin-films deposited by MBE, and was found to significantly impact the performance of MESFETs comprising these thin-films [98,106]. Recently, it has been reported that a number of defects are created in β-Ga 2 O 3 at elevated temperatures when an electrical field is present inside the material [104]. This finding has great implications for β-Ga 2 O 3 -based devices and their longterm operation.…”
Section: Influence Of Defects On the Electrical Propertiesmentioning
confidence: 98%
“…The active region usually comprises n-type β-Ga 2 O 3 , and thus, defects with charge state transition levels far away from E C are considered to be deep-level defects. Deep-level defects can either be present in as-grown β-Ga 2 O 3 [91,[98][99][100], are created during fabrication [101] or diffuse in from adjacent layers during fabrication as well as operation [98,[102][103][104] (see Fig. 4.1).…”
Section: Monoclinic Gallium Sesquioxidementioning
confidence: 99%
“…The position of the Fermi level can have a pronounced influence on defect formation processes via the contribution of the electron chemical potential to defect formation energies [21][22][23]. Particularly, it has been shown that several defect signatures are introduced in the space-charge region of β-Ga 2 O 3 Schottky barrier diodes (SBDs) when the diodes are exposed to elevated temperatures in conjunction with an applied bias voltage, causing a change in the Fermi-level position within the space-charge region [24]. Moreover, hydrogen (H) can play an important role in defect formation because H is expected to be mobile at or slightly above room temperature in β-Ga 2 O 3 , and has been shown to form complexes with various acceptor defects [23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…35 and we add E14-16 here in this work. The UID sample shows four majority defects located at For negative majority emission transients, the energy levels obtained from DLTS measurements can vary depending on the electrical field in which the defect sits during the measurement phase of the experiment which in turn changes as a function of built-in and applied bias and doping density 20,30,34,38 . As shown in Fig.2b, the DLTS signals in the UID sample shift toward lower temperature and the asymmetric tails at lower temperature side enlarge for increasing reverse biaseseffects which are more pronounced for the #1 Zr doped sample (Fig.2c).…”
mentioning
confidence: 99%
“…For negative majority emission transients, the energy levels obtained from DLTS measurements can vary depending on the electrical field in which the defect sits during the measurement phase of the experiment which in turn changes as a function of built-in and applied bias and doping density 20,30,34,38 . As shown in Fig.…”
mentioning
confidence: 99%